PELAKSANAAN STRATEGI YAYASAN WAHA MITRA INDONESIA DALAM MENINGKATKAN PELAYANAN PROGRAM AIR BERSIH DI KOTA PEKANBARU - ", Murni; Zaili, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of strategy Waha Mitra Indonesia Foundation to increase the savewater service at Pekanbaru city. As for the purpose of this research was to know and to analyzedhow the implementation of strategy and any factors that influence the implementation of strategyof Waha Mitra Indonesia Foundation to increase help for save water program in Pekanbaru city.This research used descriptive qualitative method and located in Waha Mitra IndonesiaFoundation at Pekanbaru city and as the key informan is Leader of Waha Mitra IndonesiaFoundation and others addition informans. In collect the data, this research used interviews,observation and documentation techniques. The result of this research found that theimplementation of strategy Waha Mitra Indonesia Foundation was not been implementmaximally. It can see from some of the strategies hadn’t been doing well, as an example in SaveWater Comitee where the society still not enthusiasm to bound in this program and some of themdidn’t have posses and good responsibility in their own regions.Keywords: Implementation, Strategy, Save Water